Correlation between Emotional Intelligence, Impulsivity and Irrational Beliefs with Addiction Potential of Male Secondary School Students - Jamshid Zadehasan; Naser Sarraj khorrami (Hamadan University of Medical Sciences, 2019)
Aim(s): The susceptibility of people to addiction provides the platform for people to become addicted. This means that some people are more prepared for addiction than others. Therefore, attention should be paid to the underlying factors for the preparation of addiction in people. In this regard, the aim of present study was to determine the correlation between emotional intelligence, impulsivity and irrational beliefs with addiction potential in male secondary school students. Instruments & Methods: In this descriptive-correlational study, 357 male secondary school students in Dezful city in the academic year of 2016-2017 were selected using cluster random sampling. The collection tools were Bar-On Emotional Quotient Inventory, Barratt Impulsiveness Scale version 11 Questionnaire (BIS-11), Irrational Beliefs Test (IBT), and Addiction Potential Scale (APS). The data were analyzed by SPSS 21 software using Pearson correlation coefficient and stepwise multiple regression analysis. Findings: There was a negative correlation between addiction potential with the emotional intelligence, but there was a positive correlation between impulsiveness and irrational beliefs with the addiction potential (p<0.01). Also cognitive impulsiveness (β=0.63), coping with pressure (β=-0.29), and interpersonal skills (β=-0.22) could predict 46% of variance of addiction potential (p<000.1). Conclusion: Addiction potential has negative correlation with emotional intelligence and positive correlation with impulsiveness and irrational beliefs in male secondary school students.